Frame card game - a revolutionary English vocabulary game that also aids in strategizing and critical thinking / Afni Anida Adnan ... [et al.] - Adnan, Afni Anida; Azmi, Sharina Salmi; Tengku Mahmood, Tengku Farah Petri; Hassan, Fatin Aliyah; Abu Bakar, Ruhil Nadiah (Universiti Teknologi MARA, Kedah, 2023)
Vocabulary building or possessing a good pool of words, especially in English, is a prevalent problem amongst students, due to lack of reading and social communication. In UiTM, vocabulary-based questions are taught and tested in many English Language Courses (ELC) codes especially those pertaining reading, such as Integrated Language Skills: Reading and English for Critical Academic Reading Skills. To overcome this problem and to encourage students to learn and look up new words in English, the FRAME card game was designed. FRAME’s objective is more than vocabulary enhancing; the novelty of this game lies in the fact that it also requires students to apply reasoning, calculation, strategy and English skills to emerge champions. In fact, the game is named as such as it incorporates elements of Fun, Reasoning, Alertness, Mathematics and English. This game, which can be played by 4-5 players, requires the players to think strategically of which colour and letter to place before forming a word, as it will also determine the number of cards to draw. Besides being tested at other universities such as Universiti Malaya with Teaching of English as a Second Language (TESL) students, this game has also been tested amongst society members at various gameplays organized by The Tabletop Gaming Society of Malaysia. Through these gameplays, the researchers have gained valuable feedback and a very encouraging amount of interested parties wanting to commercialize the game. This shows that FRAME does not only have value as a vocabulary building teaching aid, but also as a fun game for all, with high commercialization potential.